2015
DOI: 10.4172/2157-7579.1000265
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Ovine Brucellosis in East and West Shewa Zones of Oromia Regional State, Central Ethiopia

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
1
1
Order By: Relevance
“…The present study was following the previous investigations of 29 , 34 those who reported that seroprevalence of ovine brucellosis was significantly different among the flock size categories (small, medium and large) and seroprevalence increases with flock size in Ethiopia. Another previous study was also evidenced that lower seroprevalence in small flocks compared to medium-sized and large-sized flocks 35 from other countries elsewhere.…”
Section: Discussionsupporting
confidence: 51%
“…The present study was following the previous investigations of 29 , 34 those who reported that seroprevalence of ovine brucellosis was significantly different among the flock size categories (small, medium and large) and seroprevalence increases with flock size in Ethiopia. Another previous study was also evidenced that lower seroprevalence in small flocks compared to medium-sized and large-sized flocks 35 from other countries elsewhere.…”
Section: Discussionsupporting
confidence: 51%
“…In the present study, the overall flock and individual sero-prevalence of T. gondii infection (92.7% and 45.3%) were higher than that (70.5% and 31.6%) reported in Ethiopia [24]. In this study, the sero-prevalence of T. gondii infection in dairy cattle at herd and individual level (95.5% and 40.9) were found to be higher than that (87.5% and 7.8%) of French beef cattle [25].…”
Section: Discussioncontrasting
confidence: 82%
“…It is important to identify the actual causes in the aborting sheep and goats and/ or in the aborted fetus or placental tissues to confirm the pathogen is accountable for abortion (Morris et al, 2018). This result is in line with the reports of Gebremedhin (2015) and Wubishet et al (2017), who reported that the risk of Brucella seropositivity was not associated with abortion. However, this result is inconsistent with some previous studies in Ethiopia (Tassew and Kassahun, 2014;Asmare et al, 2013) that stated brucellosis was associated with abortion in sheep and goats.…”
Section: Discussionsupporting
confidence: 77%